Risk Factors Related to Seroprevalence of Virus Hepatitis E During Pregnancy - Mohammed, Zinah S.; Mohammed, Reem L. (Scientific Journal of Medical Research, 2023)
Background: The hepatitis E virus the main as result of the severe course of viral hepatitis in worldwide acute hepatitis. Pregnant women are more vulnerable to infection because their mortality rate might exceed 25%. It is unknown how common the hepatitis E virus is among expectant mothers in MOSUL. Aims: In this study, a group of pregnant women in MOSUL City were examined to determine the seroprevalence of infection with the Hepatitis E Virus. Methods: 350 expecting mothers from MOSUL were enrolled in the study overall. Serawas tested to determine the presence of IgG antibodies against the hepatitis E virus using the ELISA technique. The women’s sociodemographic information was acquired, along with information on their virus hepatitis E risk factors (interaction with animals, blood transfusions, and drinking water sources). Results: Hepatitis E virus positivity was found in just one lady, yielding a prevalence of 0.28%. She reported not having been had good living conditions and were not being exposed to any hepatitis E virus infection risk factors, a high socioeconomic status, and a high level of education. The majority of the ladies (67.9%) were from middle-class or upper-class families; 36.6% had a college degree; and 50.4% drank bottled water. Only a small percentage were exposed to risk factors for hepatitis E virus infection: 2.9% had received blood transfusions, and 11.4% had direct contact with animals. Conclusion: Hepatitis E virus infection was incredibly rare in the sample (0.28%) More epidemiological studies in various population groups are required to determine the MOSUL’s overall hepatitis E virus prevalence.